IMPLEMENTASI MENINGKATKAN IMUNITAS TUBUH MELALUI SENAM IRAMA DAN EDUKASI KEBUTUHAN GIZI DI DESA PANTAI MEKAR - Andhika Muhamad Firdaus; Hasan Basri (An-Nizam, 2023)
The lack of understanding of the people of Pantai Mekar Village, Muara Gembong Subdistrict, regarding the importance of maintaining health and increasing body immunity by light exercise makes the community vulnerable to disease. Community service activities aim to improve the health and immunity of the people of Pantai Mekar Village by doing rhythmic gymnastics. The method of implementing community service applies socialization and counseling methods related to rhythmic gymnastics to the local community which aims to increase understanding and awareness of the people of Pantai Mekar Village about the importance of maintaining and increasing body immunity and educating the community about the importance of maintaining a balanced nutritional intake for adolescents to the elderly. The results of this activity have a positive impact on activity participants in the form of insight, knowledge and abilities about the importance of routinely doing rhythmic gymnastics, and applying the principles of balanced nutrition to increase body immunity.